Fluorine-doped graphene as triboelectric material. (1st October 2022) - Molina-García, Miguel Ángel; Sofer, Zdeněk; Panda, Jaya Kumar; Serri, Michele; Salerno, Marco; Marras, Sergio; Lauciello, Simone; Plutnar, Jan; Bonaccorso, Francesco
Abstract: The optimization of the triboelectric layer is of paramount importance for the improvement of the performance of triboelectric nanogenerators (TENGs). In this work, we present an innovative approach exploiting the addition of highly electronegative fluorine-doped reduced graphene oxide (F-RGO) flakes into a polydimethylsiloxane (PDMS) polymeric matrix acting as the tribonegative frictional layer. The resulting layer (F-RGO/PDMS) is incorporated into a vertical contact-separation mode TENG. The optimization of the F-RGO/PDMS composition, with a F-RGO content of 2%, delivered a ten times higher power density peak compared to a F-RGO-free device. The outstanding enhancement of the power density peak is attributed to the synergistic effect of the high electronegativity of the fluorine atoms and the triboelectric properties of the graphene-based flakes. Endurance tests confirmed the stability of the F-RGO/PDMS system, demonstrating its suitability for long-lasting TENG-based wearable devices.